From Christ To The World - Boulton, G ,Wayne (2010)
"Designed specifically to provide full-orbed instruction in the discipline of Christian ethics, this unique introductory reader surveys the many exciting and timely issues in the field of Christian ethics while simultaneously presenting the fundamentals
Keywords: Christian ethics